CHARACTERIZATION OF THE INTERNAL EFFICIENCY OF PUBLIC UNIVERSITY STUDENTS USING INDICATORS OF EDUCATIONAL QUALITY MODELS - Author (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Speaking of quality is a topic very important in all organizations because the success of its management depends on it; however, it is even more important to talk about quality in education, the result of which are the professionals who will lead the organizations. The internal efficiency measures and evaluates annually through indicators the situation of the student in the development of their activities in the educational exercise. Taking the quality model of SINEACE as a reference in this work in comparison with other quality models, we talk about the evaluation of internal efficiency within the Accounting and Electrical Engineering programs.